Concepts and operationalization of pro-poor growth - Mario Negre (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Growth that reduces poverty is often considered pro-poor regardless of whether the poor benefit from it more than the non-poor. Such growth could simply be termed poverty-reducing growth. This paper argues that for growth to be pro-poor it should disproportionally benefit the poor. The paper proposes an operational definition of pro-poor growth that restricts it to the cases in which the mean income of the poor increases proportionally more than that of the non-poor. A new index is proposed based exclusively on the redistributional component of poverty-gap changes obtained through an exact decomposition. It is then shown that this component measures how pro-poor growth is over a given period based on the above mentioned definition. The paper further presents several indicators for evaluating and monitoring the 'pro-poorness' of growth over time and concludes with an empirical illustration for the case of Honduras.
Keywords: C16; D31; D63; I32; O15; O54; 330; pro-poor; growth; income; inequality; poverty decomposition; Honduras